2005
DOI: 10.1093/hmg/ddi247
|View full text |Cite
|
Sign up to set email alerts
|

Extensive polymorphisms of LILRB1 (ILT2, LIR1) and their association with HLA-DRB1 shared epitope negative rheumatoid arthritis

Abstract: Leukocyte immunoglobulin-like receptor subfamily B member 1 (LILRB1/LIR1/ILT2) is an inhibitory receptor broadly expressed on leukocytes and recognizes HLA-class I and human cytomegalovirus UL18. LILRB1 is encoded within the leukocyte receptor complex on 19q13.4, previously implicated to be a susceptibility region to systemic lupus erythematosus (SLE). In this study, we screened for polymorphisms of LILRB1 and examined their association with SLE and rheumatoid arthritis (RA). In the 5' portion of LILRB1, three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 45 publications
7
94
2
Order By: Relevance
“…Therefore, it is possible that the cis interaction influences trans NK-cell ligand recognition and binding in individuals expressing higher or lower levels of LIR-1 and with various polymorphisms [8]. Although the effect of D1D2 polymorphisms on HLA-class I binding in trans was reported to be minimal in a previous study [38], polymorphisms could alter the cis interaction. Gaining a better understanding of the mechanisms involved in regulating LIR-1 signaling and function will provide further insight into the susceptibility of individuals to infections such as HCMV.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it is possible that the cis interaction influences trans NK-cell ligand recognition and binding in individuals expressing higher or lower levels of LIR-1 and with various polymorphisms [8]. Although the effect of D1D2 polymorphisms on HLA-class I binding in trans was reported to be minimal in a previous study [38], polymorphisms could alter the cis interaction. Gaining a better understanding of the mechanisms involved in regulating LIR-1 signaling and function will provide further insight into the susceptibility of individuals to infections such as HCMV.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that this gene is highly polymorphic (24) and can be alternatively spliced (25). However, a recent genome-wide association study did not reveal a significant association between LILRB1 and dengue shock syndrome (26); this is not surprising because, although LILRB1 activation is critical for initial replication with FcγR-mediated entry, multiple other host and viral factors contribute to eventual disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…ILTs are encoded by multiple genes with many polymorphisms (22,36,37), some of which may affect individual susceptibility to bacteria infection. Interestingly, several recent reports suggest that ILT polymorphisms are associated with some autoimmune diseases including rheumatoid arthritis (42)(43)(44). Thus, alteration of immune homeostasis by disruption of one member of an ILT pair may contribute to an increased risk for autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%